2007
DOI: 10.1021/ma070927k
|View full text |Cite
|
Sign up to set email alerts
|

Post-Polymerization Functionalization Approach for Highly Water-Soluble Well-Defined Regioregular Head-to-Tail Glycopolythiophenes

Abstract: Two bromide-bearing regioregular head-to-tail polythiophenes (polymers 1 and 3) were prepared by using Grignard metathesis method to polymerize 2,5-dibromo-3-bromohexylthiophene (2) and 2,5-dibromo-3-(11-bromo-3,6,9-trioxa-1-undecoxy)thiophene ( 7), respectively. Well-defined regioregular head-to-tail glycopolythiophenes were prepared through post-polymerization functionalization approach by treating the bromidebearing polythiophenes with 1-thiolethyl-R-D-mannose tetraacetate (3a) or 1-thiol-β-D-glucose tetraa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 34 publications
1
30
1
Order By: Relevance
“…5). When all other variables are kept constant, the higher K SV means the lower concentration of quencher is required to quench the fluorescence [11,19,30]. These results revealed that PNA can selectively bind to polymer P-2 based on multivalent interactions.…”
Section: Response To Lectinsmentioning
confidence: 85%
See 4 more Smart Citations
“…5). When all other variables are kept constant, the higher K SV means the lower concentration of quencher is required to quench the fluorescence [11,19,30]. These results revealed that PNA can selectively bind to polymer P-2 based on multivalent interactions.…”
Section: Response To Lectinsmentioning
confidence: 85%
“…where I 0 is the fluorescent intensity in the absence of quencher, I is the fluorescent intensity as a function of quencher concentration [Q], and K SV is the Stern-Volmer constant, defining the efficiency of quenching [11,19,30]. The Stern-Volmer quenching constant of polymer P-2 by PNA was calculated as 1.56 Â 10 5 M À1 based on the linear part of the curve (Fig.…”
Section: Response To Lectinsmentioning
confidence: 99%
See 3 more Smart Citations